Distinguishing Social From Private Intentions Through the Passive Observation of Gaze Cues - Jording, Mathis; Engemann, Denis; Eckert, Hannah; Bente, Gary; Vogeley, Kai (Frontiers in Human Neuroscience, 2019)
Observing others’ gaze is most informative during social encounters between humans: We can learn about potentially salient objects in the shared environment, infer others’ mental states and detect their communicative intentions. We almost automatically follow the gaze of others in order to check the relevance of the target of the other´s attention. This phenomenon called gaze cueing can be conceptualized as a triadic interaction involving a gaze initiator, a gaze follower and a gaze target, i.e. an object or person of interest in the environment. Gaze cueing can occur as “gaze pointing” with a communicative or “social” intention by the initiator, telling the observer that she/he is meant to follow, or as an incidental event, in which the observer follows spontaneously without any intention of the observed person. Here, we investigate which gaze cues let an observer ascribe a social intention to the observed person’s gaze and whether and to which degree previous eye contact in combination with an object fixation contributes to this ascription. We varied the orientation of the starting position of gaze towards the observer and the orientation of the end position of a lateral gaze shift. In two experiments participants had to infer from the gaze behavior either mere approach (“the person looked at me”) vs. a social (“the person wanted to show me something”) or a social vs. a private motivation (“the person was interested in something”). Participants differentially attributed either approach behavior, a social, or a private intention to the agent solely based on the passive observation of the two specific gaze cues of start and end position. While for the attribution of privately motivated behavior, participants relied solely on the end position of the gaze shift, the social interpretation of the observed behavior depended additionally upon initial eye contact. Implications of these results for future social gaze and social cognition research in general are discussed.